Benefit of Chemoradiotherapy Versus Chemotherapy After Induction Therapy for Conversion of Unresectable Into Resectable Pancreatic Cancer: The Randomized CONKO-007 Trial - Fietkau, Rainer; Ghadimi, Michael; Grützmann, Robert; Wittel, Uwe A.; Jacobasch, Lutz; Uhl, Waldemar; Croner, Roland S.; Bechstein, Wolf Otto; Neumann, Ulf Peter; Waldschmidt, Dirk; Boeck, Stefan; Moosmann, Nicolas; et al. (Journal of Clinical Oncology, 2025)
PURPOSE To determine the benefit, measured as complete removal of a tumor so that no tumor cells are detectable during histopathologic examination of the resection margin (R0 resection rate), of induction chemotherapy plus chemoradiotherapy (CRT) compared with chemotherapy alone for unresectable pancreatic tumors. PATIENTS AND CONKO-007, an investigator-initiated open-label, multicentric, phase III METHODS randomized clinical trial, enrolled 525 patients with unresectable tumors, and 495 patients received induction chemotherapy (402 with fluorouracil, irinotecan, and oxaliplatin [FOLFIRINOX] and 93 with gemcitabine). Patients without progression after 3 months of induction chemotherapy (n 5 336) were randomly assigned for continuation of the same chemotherapy (n 5 167) or CRT (n 5 169; 50.4Gy concurrently with gemcitabine). Resectability was centrally reassessed by a panel of surgeons. Surgery was recommended if possible. After an interim analysis, the primary end point was changed from overall survival (OS) to overall R0 resection rate because of slow recruitment. The median follow-up was 76 months. Important planned secondary end points were R0 resection rate in the surgically treated population and OS. RESULTS The primary end point (overall R0 resection rate) was not significantly different between treatment arms with 25% (43 of 169) in the CRT arm versus 18% in the chemotherapy arm (30 of 167; P 5 .113). Secondary end point analysis showed that surgery was performed equally often (P 5 .91); R0 resection rate in patients who underwent surgery was higher after CRT, 69.4% (43 of 62) compared with chemotherapy alone: 50.0% (30 of 60 patients, P 5 .04). Other parameters of resection (ratio of R0/R1/R2/no resection) also favored CRT (P 5 .02). No difference in OS was seen between treatment arms (hazard ratio [HR], 0.937 [95% CI, 0.747 to 1.174]; P 5 .57; randomly assigned intention-to-treat patients). Surgery was associated with longer OS (P < .001, HR, 0.525 [95% CI, 0.408 to 0.676]). CONCLUSION Although not improving overall R0 resection rate or survival, CRT enables a R0 resection in surgically treated patients more often than chemotherapy alone.
CRIS-Team Scopus Importer:2025-08-29

Change in Quality of Life in Patients with Advanced Rectal Cancer Between 2010 and 2022 - Dölz, Ailina; Blasko, Daniel; Schweizer, Claudia; Fitz, Tim; Kallies, Annett; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2024)
Background/Objectives: Advanced rectal cancer is one of the most common cancers worldwide and has a significant impact on public health. Because favorable and long-term survival has been achieved with multimodal therapy, patient quality of life is very important. The intention of this study was to assess patients’ quality of life using various functioning and symptom scores from the years 2010 to 2022 and to examine changes over time. Methods: Data on health-related quality of life were collected from rectal cancer patients treated at the University Hospital Erlangen in Germany over a period of 13 years. The EORTC QLQ-C30 questionnaire and the rectal cancer-specific module QLQ-CR38 were completed in this study by a total of 516 patients. The questionnaires were collected before, during and at annual follow-up visits after treatment. Statistical significance was defined as p-values < 0.05 as well as a difference of 10 or more percentage points. Results: The deterioration in scores is most pronounced immediately after radiochemotherapy, especially for pain (+19.8 pp), fatigue (+16.1 pp) and diarrhoea (+24.8 pp). One year after the end of therapy, most of the values are again comparable to or better than those of the German general population and only role functioning (−19.8 pp), social functioning (−24.6 pp), diarrhoea (−21.6 pp) and financial difficulties (−16.3 pp) are considerably worse. Some baselines deteriorate clearly over time from 2010 to 2022; these are role functioning (−23.9 pp), social functioning (−17.3 pp), body image (−15.2 pp), fatigue (+13.8 pp) and nausea and vomiting (+10.5 pp). Conclusions: An improvement in therapy in terms of a reduction in side effects and, thus, an improvement in quality of life over time could not be proven. The deterioration in individual scores over time does not appear to be a problem specific to rectal cancer patients, but rather, is associated with social developments or systemic healthcare factors in German society that are not directly related to oncological diseases.
CRIS-Team Scopus Importer:2025-02-04
Keywords: health-related quality of life; long-term follow-up; neoadjuvant; QLQ-C30; radiochemotherapy; rectal cancer

Differences and Similarities in the Pattern of Early Metabolic and Morphologic Response after Induction Chemo-Immunotherapy versus Induction Chemotherapy Alone in Locally Advanced Squamous Cell Head and Neck Cancer - Beck, Michael; Semrau, Sabine; Haderlein, Marlen; Gostian, Antoniu-Oreste; Hartwich, Julius; Müller, Sarina Katrin; Kallies, Annett; Geppert, Carol-Immanuel; Schonath, Miriam; Putz, Florian; Gaipl, Udo; Frey, Benjamin; et al. (Cancers, 2022)
Simple Summary There are differences and similarities when assessing the short-term therapeutic response of chemotherapy and chemotherapy plus immunotherapy using imaging techniques, which may be necessary to make treatment decisions in malignant head and neck tumors. After both chemo- and immunochemotherapy, remission becomes measurable in cross-sectional and metabolic diagnostics after only one cycle of therapy, with (18)FDG-PET/CT predicting complete remission of tumor cells in a representative biopsy better than MRI/CT examination in both therapeutic modalities. While complete tumor remission is highly likely (88%) after immunochemotherapy in tumors with low residual activity (<= 40% of initial SUV), this is less common after chemotherapy alone (65%). In metabolic nonresponse with more than 80% residual activity, the probability of complete remission nevertheless is low after chemotherapy alone (6%). After immunochemotherapy, these false nonresponders are common (35%), requiring additional diagnostics by deep biopsy. Cases of pseudoprogression with an increase of SUVmax of more than 125% of the baseline were not observed. Background: In head and neck cancer patients, parameters of metabolic and morphologic response of the tumor to single-cycle induction chemotherapy (IC) with docetaxel, cis- or carboplatin are used to decide the further course of treatment. This study investigated the effect of adding a double immune checkpoint blockade (DICB) of tremelimumab and durvalumab to IC on imaging parameters and their significance with regard to tumor cell remission. Methods: Response variables of 53 patients treated with IC+DICB (ICIT) were compared with those of 104 who received IC alone. Three weeks after one cycle, pathologic and, in some cases, clinical and endoscopic primary tumor responses were evaluated and correlated with a change in 18F-FDG PET and CT/MRI-based maximum-standardized uptake values (SUVmax) before (SUV(max)pre), after treatment (SUV(max)post) and residually (resSUV(max) in % of SUV(max)pre), and in maximum tumor diameter (D-max) before (D(max)pre) and after treatment (D(max)post) and residually (resD). Results: Reduction of SUVmax and D-max occurred in both groups; values were SUV(max)pre: 14.4, SUV(max)post: 6.6, D(max)pre: 30 mm and D(max)post: 23 mm for ICIT versus SUV(max)pre: 16.5, SUV(max)post: 6.4, D(max)pre: 21 mm, and D(max)post: 16 mm for IC alone (all p < 0.05). ResSUV(max) was the best predictor of complete response (IC: AUC: 0.77; ICIT: AUC: 0.76). Metabolic responders with resSUV(max) <= 40% tended to have a higher rate of CR to ICIT (88%; n = 15/17) than to IC (65%; n = 30/46; p = 0.11). Of the metabolic nonresponders (resSUV(max) > 80%), 33% (n = 5/15) achieved a clinical CR to ICIT versus 6% (n = 1/15) to IC (p = 0.01). Conclusions: ICIT and IC quickly induce a response and 18F-FDG PET is the more accurate modality for identifying complete remission. The rate of discrepant response, i.e., pCR with metabolic nonresponse after ICIT was >30%.
CRIS-Team WoS Importer:2022-10-21

Impact of COVID-19 on Quality of Life in Long-Term Advanced Rectal Cancer Survivors - Blasko, Daniel; Schweizer, Claudia; Fitz, Tim; Schröter, Christoph; Sörgel, Christopher; Kallies, Annett; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2023)
Colorectal cancer remains one of the most commonly diagnosed cancers. Advanced rectal cancer patients receive neoadjuvant radiochemotherapy as well as surgery and suffer from reduced health-related quality of life due to various side effects. We were interested in the role of the COVID-19 pandemic and how it affected those patients’ quality of life. A total of 489 advanced rectal cancer patients from the University Hospital Erlangen in Germany were surveyed between May 2010 and March 2022 and asked to fill out the EORTC QLQ-C30 and QLQ-CR38 questionnaires over eight different time points: at the beginning, during and after radiochemotherapy, right before surgery, and in yearly intervals after surgery for up to four years. Answers were converted to scores to compare the COVID-19 period to the time before March 2020, focusing on the follow-ups, the developments over time—including by sex and age—and the influence of the TNM cT-stage. Overall, a trend of impaired functional and symptom scores was found across all surveys with few significances (body image −10.6 percentage points (pp) after one year; defecation problems +13.5 pp, insomnia +10.2 pp and weight loss +9.8 pp after three years; defecation problems +11.3 pp after four years). cT4-stage patients lost significantly more weight than their cT1-3-stage counterparts (+10.7 to 13.7 pp). Further studies should be conducted to find possible causes and develop countermeasures for future major infectious diseases.
CRIS-Team Scopus Importer:2023-08-11
Keywords: COVID-19; pandemic; quality of life; radiochemotherapy; rectal cancer

Pathologic response after induction chemo-immunotherapy with single or double immune checkpoint inhibition in locally advanced head and neck squamous cell carcinoma (HNSCC): Expansion cohorts of the CheckRad-CD8 trial. - Hecht, Markus; Eckstein, Markus; Kallies, Annett; Klautke, Gunther; Illmer, Thomas; von der Grün, Jens; Laban, Simon; Hautmann, Matthias; Tamaskovics, Bálint; Hinke, Axel; Brunner, Thomas; Frey, Benjamin; et al. (JOURNAL OF CLINICAL ONCOLOGY, 2022)
CRIS-Team WoS Importer:2022-11-04

Pilot Project for App-based Patient Connection in outpatient Tumor Therapy - Hecht, Markus; Goldbrunner, L.; Kaul, F.; Winkler, S.; Ploner, N.; Lettmaier, Sebastian; Haderlein, Marlen; Kallies, Annett; Pirschel, Wiebke; Fietkau, Rainer; Distel, Luitpold (STRAHLENTHERAPIE UND ONKOLOGIE, 2022)
CRIS-Team WoS Importer:2022-06-03

Substantial Impairment of Quality of Life during COVID-19 Pandemic in Patients with Advanced Rectal Cancer - Dennison, Irene; Schweizer, Claudia; Fitz, Tim; Blasko, Daniel; Sörgel, Christopher; Kallies, Annett; Schmidt, Linda; Fietkau, Rainer; Distel, Luitpold (Healthcare, 2022)
The aim of this study was to analyze the quality of life of patients with advanced rectal cancer before and during the COVID-19 pandemic and to determine whether the pandemic affected patients' quality of life. The study included 389 patients and was performed from May 2010 to June 2021. The fifteen months from March 2020 to June 2021 were categorized as the COVID-19 period. Patients were surveyed using the QLQ-C30 and QLQ-CR38 questionnaires. The questionnaires were used at different phases of radiochemotherapy: prior to RCT (day 1), during RCT (day 14), at the end of RCT (day 35), and prior to mesorectal surgery (day 70). Scores were formed from the questions. In addition, scores were analyzed for different age groups (64) and sexes (female and male). Overall, patients reported lower functional scores and higher symptom scores during the pandemic than before the pandemic. Although it had been expected that older and younger patients would differ clearly, there were only minor differences. The comparison between the two sexes showed very different scores, with female patients having lower functional scores and higher symptom scores than male patients before and especially during COVID-19. In conclusion, age does not play a major role in quality of life, but sex does play an important role in perception of functioning and symptoms. COVID-19 also had a major impact on patients' lives, as it was a very isolating and stressful time for everyone, especially cancer patients, which was reflected in worsening scores.
CRIS-Team WoS Importer:2022-09-09

The health-related quality of life of sarcoma patients treated with neoadjuvant versus adjuvant radiotherapy – Results of a multi-center observational study - Singer, Susanne; Semrau, Sabine; Golcher, Henriette; Fechner, Katja; Kallies, Annett; Zapata Bonilla, Sergio; Grützmann, Robert; Fietkau, Rainer; Kluba, Torsten; Jentsch, Christina; Andreou, Dimosthenis; Bornhäuser, Martin; et al. (Radiotherapy and Oncology, 2023)
Aim: The sequence of radiotherapy and resection in patients with soft tissue sarcomas is usually discussed on an individual basis. Better understanding of potential differences of health-related quality of life (QoL) between patients undergoing adjuvant (ART) versus neoadjuvant radiotherapy (NART) is therefore helpful for clinical decision making. Methods: Adult sarcoma patients from 39 hospitals completed the European Organisation for Research and Treatment of Cancer Quality of Life Core Questionnaire (EORTC QLQ-C30). Differences in global QoL, physical functioning, role functioning, fatigue, pain, and insomnia between ART versus NART were investigated with multivariate regression, adjusting for age, gender, chemotherapy, grading, stage, tumor location, recurrence/distant metastasis, sarcoma type, time since last treatment, and treatment status using validated thresholds. Results: A total of 1110 patients participated. Of them, 340 had received radiotherapy (NART: n = 95, 28%; ART: n = 245, 72%). Global QoL was 59.3 on average after NART and 60.5 after ART (Badj = 1.0, p = 0.74). Physical functioning was 65.9 compared to 70.5 (Badj = 4.2; p = 0.16), role function 48.8 vs. 56.7 (Badj = 7.0, p = 0.08), fatigue 47.5 vs. 45.4 (Badj = -1.2; p = 0.71), pain 40.2 vs. 34.1 (Badj = -6.8; p = 0.08), and insomnia 33.7 vs. 41.6 (Badj = 5.5, p = 0.16). Among patients with NART, clinically relevant QoL impairments were less frequent 2 years after treatment compared to < 2 years thereafter (n = 6 vs. n = 4 on average). Conclusion: There is little evidence for QoL differences in most domains and overall QoL between the two irradiation groups. However, patients after NART might experience worse role functioning and pain but fewer problems with insomnia compared to patients after ART.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Leiomyosarcoma; Liposarcoma; Neoadjuvant Therapy; Neoplasms; Connective and Soft Tissue; Patient Reported Outcome Measures; Radiotherapy; Adjuvant

Updated analysis of the phase II CheckRad-CD8 trial: First-line treatment of locally advanced head and neck squamous cell carcinoma with induction chemoimmunotherapy followed by radioimmunotherapy - Hecht, Markus; Eckstein, Markus; Kallies, Annett; von der Grün, Jens; Illmer, Thomas; Klautke, Gunther; Laban, Simon; Hautmann, Matthias; Brunner, Thomas; Tamaskovics, Bálint; Hinke, Axel; Zhou, Jianguo; et al. (35. Deutscher Krebskongress, Krebsmedizin: Schnittstellen zwischen Innovation und Versorgung, 2022)
CRIS-Team WoS Importer:2022-12-16